Scholar in the Wilderness Francis Adrian Van der Kemp - Jackson, Harry (Syracuse University Press, 1963)
When Thomas Jefferson wrote to John Adams: "There is a Mr. Vanderkemp of New York, a correspondent, I believe, of yours, with whom I have exchanged some letters, without knowing who he is. Will you tell me?" Adams replied: "The biography of Mr. Vanderkemp would require a volume...My acquaintance with him began at Leyden, in 1780. He was the minister of the Mennonite congregation, the richest in Europe, in that city, where he was celebrated as the most elegant writer in the Dutch language... In 1788 when the king of Prussia threatened Holland with invasion, his party insisted on his taking a command of the most exposed and most important post in the seven provinces. He was soon surrounded by the Prussian forces, but he defended his fortress...till, abandoned by his nation, destitute of provisions and ammunition, still refusing to surrender, he was offered the most honorable capitulation...despairing of the liberty of his country, he ...determined to emigrate to New York; he wrote to me...requesting letters of introduction. I sent him letters to Governor Clinton and several others of our little great men. His history in this country is equally curious and affecting.... His head is deeply learned, and his heart is pure... 'he is a mountain of salt to the earth,'...Had he been as great a master of our language as he was of his own, he would at this day have been one of the most conspicuous characters in the United States." Francis Adrian Van der Kemp was a writer, minister, and political leader of some prominence in his native Holland when he fled from religious and political persecution in 1788 to settle in Oneida County in upstate New York. He became one of the area's important citizens during its formative period. His active, inquiring mind ranged far beyond his rural village of Oldenbarneveld. Politics, religion, history, government, scientific agriculture geology, the Erie Canal, the conduct of the War of 1812, and any threat to political or religious freedom stimulated him to research and writing. Van der Kemp's views were sought and respected not only by his friends and neighbors, but by state and national leaders as well. His warm friendship with John and Abigail Adams endured till their deaths, and John Quincy Adams continued the friendship. This is an absorbing biography of an active and influential citizen and resident of central New York State.